Level of Detail and Level of Development: Commissioning processes and Information Modelling - Ciribini, Angelo (TECHNE - Journal of Technology for Architecture and Environment, 2013)
The essence of Information Modelling in the Construction Industry lies in the methods of evolution of the information content through the lifecycle of the commission and the work. Such progress in the levels of development of the model is profoundly different from normal progress as it is strongly affected by the goals of whoever is managing the Information Model itself. The subjects that appear to benefit most from this seem to be governments, delegated project contractors, authorities or promoters and finally and in particular, lenders.